Macrophages in Atheromatous Plaque Developmental Stages - von Ehr, Alexander; Bode, Christoph; Hilgendorf, Ingo (Frontiers in Cardiovascular Medicine, 2022)
Atherosclerosis is the main pathomechanism leading to cardiovascular diseases such as myocardial infarction or stroke. There is consensus that atherosclerosis is not only a metabolic disorder but more a chronic inflammatory disease under the influence of various immune cells of the innate and adaptive immune system. Macrophages constitute the largest population of inflammatory cells in atherosclerotic lesions. They play a critical role in all stages of atherogenesis. The heterogenous macrophage population can be subdivided on the basis of their origins into resident, yolk sac and fetal liver monocyte-derived macrophages and postnatal monocyte-derived, recruited macrophages. Recent transcriptomic analyses revealed that the major macrophage populations in atherosclerosis include resident, inflammatory and foamy macrophages, leading to a more functional approach. The aim of this review is to provide an overview of the trafficking, fate, and functional aspects of the different macrophage populations in the ‘life cycle’ of an atheromatous plaque. Understanding the chronic inflammatory state in atherosclerotic lesions is an important basis for developing new therapeutic approaches to abolish lesion growth and promote plaque regression in addition to general cholesterol lowering.